A Naturalistic Explanation of Miracles: The Case of Ibn Sina - ACAR, RAHİM (UNIV TORONTO PRESS INC, 2017)
In this article I focus on Ibn Sn's explanation of miracles and argue that he accepts the occurrence of miracles as extraordinary events, despite his theory of the necessity of everything. His explanation of miracles may be considered naturalistic, since it does not require an exceptional divine intervention. First, I analyze Ibn Sn's theory of miracles, then I relate it to his explanation of the functioning of the universe. I try to answer how it might be possible to accept both the necessary causal nexus within the world and the occurrence of miracles as violations of the natural laws. Finally, I take into account al-Ghazl's critique of philosophers, including Ibn Sn, on their acceptance of a necessary connection between causes and effects, a critique supposedly aimed at saving the possibility and actual occurrence of miracles. I try to make sense of al-Ghazls text, vis-a-vis the fact that Ibn Sina did not deny the occurrence of miracles, and the fact that his theory provides a possible explanation thereof. Hence, I argue that the real issue between al-Ghazli and the philosophers he attacked regarding the purportedly necessary connection between causes and effects is not the possibility of miracles, but the proper conception of God.
Keywords: Ibn Sina; miracles; naturalistic explanation; al-Ghazali; conception of God; CAUSALITY